2005
DOI: 10.1074/jbc.m503544200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Cold/Menthol-sensitive Transient Receptor Potential Melastatine Family Member 8 (TRPM8) in the Activation of Store-operated Channels in LNCaP Human Prostate Cancer Epithelial Cells

Abstract: Recent cloning of a cold/menthol-sensitive TRPM8 channel (transient receptor potential melastatine family member 8) from rodent sensory neurons has provided the molecular basis for the cold sensation. Surprisingly, the human orthologue of rodent TRPM8 also appears to be strongly expressed in the prostate and in the prostate cancer-derived epithelial cell line, LNCaP. In this study, we show that despite such expression, LNCaP cells respond to cold/menthol stimulus by membrane current (I cold/menthol ) that show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
151
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(168 citation statements)
references
References 39 publications
13
151
2
2
Order By: Relevance
“…Later studies have reported similar menthol-induced Ca 2ϩ release in TRPM8-expressing LNCaP cells and dorsal root ganglion neurons (4,7,8), leading to the hypothesis that TRPM8 can function as an intracellular Ca 2ϩ -release channel. Further support to this idea came from immunocytochemical stainings indicating that TRPM8 is significantly or even exclusively located on intracellular membranes in LNCaP cells (7,8). However, our present data indicate that these results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Later studies have reported similar menthol-induced Ca 2ϩ release in TRPM8-expressing LNCaP cells and dorsal root ganglion neurons (4,7,8), leading to the hypothesis that TRPM8 can function as an intracellular Ca 2ϩ -release channel. Further support to this idea came from immunocytochemical stainings indicating that TRPM8 is significantly or even exclusively located on intracellular membranes in LNCaP cells (7,8). However, our present data indicate that these results should be interpreted with caution.…”
Section: Discussionmentioning
confidence: 92%
“…3F). As previous studies reporting that endogenous TRPM8 in LNCaP cells is to a large extent or even fully restricted to intracellular compartments used the commercial anti-TRPM8 antibodies (7,8), we repeated immunocytochemical staining of LNCaP using our new anti-TRPM8 antibody. In contrast to the results from these previous studies, the staining pattern that we obtained was consistent with a principally plasma- lemmal localization of TRPM8 (Fig.…”
Section: Menthol-induced Ca 2ϩmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, icilin did not trigger any [Ca 2 þ ] i Figure 1 PSA activates TRPM8. (a) Representative time courses of cold-activated (22 1C) I TRPM8 under control condition (white dots) or after overnight pre-treatment with 40 ng/ml PSA (black dots) in the HEK-TRPM8-inducible cell line, cultured as previously described (Thebault et al, 2005). TRPM8 expression was induced with tetracycline 24 h before the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…(b) Cumulative data of the [Ca 2 þ ] i in HEK-TRPM8 cells in control (black column) or after overnight pre-treatment with 40 ng/ml PSA (gray column) after icilin-evoked TRMP8 Ca 2 þ entry. [Ca2 þ ]i was measured using fura-2, as previously described (Thebault et al, 2005;Bidaux et al, 2007). The same extracellular solution was used as in electrophysiological experiments.…”
Section: Resultsmentioning
confidence: 99%